Book Reviews - Reviews, Book.
Susanne Deicher and Erik Maroko, eds. Die Liste: Ordnungen von Dingen und Menschen in Ägypten (Stefan Bojowald) Nadine Grässler. Konzepte des Auges im alten Ägypten (Stefan Bojowald) Lara Weiss, ed. The Coffins of the Priests of Amun Egyptian Coffins from the 21st Dynasty in the Collection of the National Museum of Antiquities in Leiden (Aidan Dodson) Pål Steiner, Alexandros Tsakos, and Eivind Heldaas Seland, eds. From the Fjords to the Nile: Essays in Honour of Richard Holton Pierce on His 80th Birthday (Elizabeth Eltze) Bram Calcoen, in collaboration with Christiane Mu?ller-Hazenbos. TT 176: The Tomb Chapel of Userhat (Beth Ann Judas)P. Der Manuelian and Th. Schneider (eds.). Towards a New History for the Egyptian Old Kingdom (Antonio J. Morales)Peter Lacovara and Sue H. D’Auria, eds. The Mystery of the Albany Mummies (Melinda Nelson-Hurst)Wael Sherbiny. Through Hermopolitan Lenses: Studies on the So-Called Book of Two Ways in Ancient Egypt (Joshua Aaron Roberson)Jean Li. Women, Gender, and Identity in Third Intermediate Period Egypt (Amanda Jane Shaffery) doi: http://dx.doi.org/10.5913/jarce.54.2018.r017